HUBUNGAN DUKUNGAN SOSIAL TERHADAP KARAKTER REMAJA - Fitri Tsani Budiarti; Herlina " "; Yesi " Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Adolescent is a period where there is a transition childhood to adulthood. Morality development task of adolescent is to form characters. Factors affecting teenage characters is a social environment that is family, peer group, and teachers. The purpose of this research is to determine the relationship between the social support with character of adolescent in SMKN 2 Pekanbaru with descriptive correlation of research design and cross sectional approach. The sample of this research are 316 respondents were taken based on inclusion criteria using non-probability sampling technique with the type of purposive sampling. The measuring instrument used is a questionnaire. The analysis used univariate analysis to determine the frequency distribution and bivariate analysis using chi-square test. The results showed that the 148 respondent had a social support of  low, 131 respondent have need consideration/B character value (41.4%) and 17 respondent have good/A character value (5.4%).  From 168 respondents had social support of high, 109 respondents have need consideration/B character value  (34.5%) and 59 respondents have good/A character value (18.7%). Based on result of chi-square test obtained of p value (0.000) < alpha (0.05), so that there are significant relationship between the social support with character of  adolescent. Based on this study recommended to families, peer group and teachers with adolescent to increase social support in an effort to improve the character of teenagers. Keyword: Adolescent, character, social support